Polylactic acid Synthesis via Direct Polycondensation Method Using Candida rugosa Lipase Catalyst - Rahmayetty, Rahmayetty; Barleany, Dhena Ria; Suhendi, Endang; Prasetya, Bayu; Andiyani, Tuti (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2017)
Polylactic acid (PLA) is a biodegradable, biocompatible polymer and is produced from renewable natural resources. PLA synthesis through a polycondensation mechanism generally uses a metal catalyst, such as Zn and Sn oxides. The disadvantages of using metal catalysts are the contamination of products produced by the metals used so that unsafe products are used for biomedical applications and food packaging. The purpose of this research is to synthesize the safe PLA used for food packaging and biomedical applications. Polycondensation is done by pretreatment of lactic acid at 120oC for 1 hour. Diluted lactic acid is mixed with Candida rugosa lipise catalyst with a certain concentration (1, 2, 3 and 4% w / w). The mixture was heated at certain temperature (60; 80; 100 and 120oC) and vacuum pressure of 0.1 bar for 72 hours. The highest viscosity and density of PLA in this study was produced at 100oC and using 3% Candida rugosa lipase. The highest viscosity and density of PLA were 2443,9 CSt and 1231,9 mg / l respectively. Candida rugosa lipase concentration does not affect PLA yield at constant polycondensation temperature. PLA yield is affected by temperature. PLA yields at 60, 80, 100 and 120 ° C are 97.98; 97,65; 96.78; 96.13% respectively. The molecule weight of PLA at temperature 100oC for 1436-1482. Lipase concentration does not affect the molecular weight of the PLA.